2022
DOI: 10.1097/tp.0000000000004032
|View full text |Cite
|
Sign up to set email alerts
|

Successful Liver Transplantation From a SARS-CoV-2 Positive Donor to a Positive Recipient: Potential Role of Monoclonal Antibodies

Abstract: while remaining on the transplant waitlist. SARS-CoV-2-directed monoclonal antibody therapy and/or preemptive remdesivir administration may have roles in this setting; however, additional studies on strategies to mitigate donor-derived COVID-19 are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 5 publications
1
8
0
1
Order By: Relevance
“…These data complement prior smaller single‐center reports and case series and may provide assurance that, at least short‐term outcomes are not compromised by use of these organs. 7 , 8 , 9 , 10 , 11 , 13 , 20 , 21 In the context of kidney transplantation, the current study indicated no difference in rates of delayed graft function or 6‐month graft survival and the characteristics of recipients was similar between negative and positive SARS‐CoV‐2 status donors. Similarly for liver and transplant recipients, both general characteristics of recipients and 6‐month graft survival were similar by SARS‐CoV‐2 status donors.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…These data complement prior smaller single‐center reports and case series and may provide assurance that, at least short‐term outcomes are not compromised by use of these organs. 7 , 8 , 9 , 10 , 11 , 13 , 20 , 21 In the context of kidney transplantation, the current study indicated no difference in rates of delayed graft function or 6‐month graft survival and the characteristics of recipients was similar between negative and positive SARS‐CoV‐2 status donors. Similarly for liver and transplant recipients, both general characteristics of recipients and 6‐month graft survival were similar by SARS‐CoV‐2 status donors.…”
Section: Discussionmentioning
confidence: 55%
“… 7 , 8 , 9 Due to ongoing uncertainties regarding the relative risks of transplantation with donors with prior or active infections, evidence for the safe use of organs from SARS‐CoV‐2–positive donors has emerged slowly with small case series from individual centers. 8 , 10 , 11 , 12 , 13 , 14 , 15 , 16 Although early results appear promising, best practices for utilization of positive SARS‐CoV‐2 donors remain unclear. 7 , 8 , 9 , 11 , 17 , 18 , 19 …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations